LEGAL PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE AGAINST MINORS (ANALYSIS OF DECISION NUMBER 221/Pid.Sus/2024/PN MEDAN) - Rizky Aulia; T. Riza Zarzani; Abdul Rahman Maulana Siregar (PT. Sinergi Legal Publisher, 2025)
This research discusses the legal protection of child victims of sexual violence based on the analysis of Decision Number 221/Pid.Sus/2024/PN Medan. In the Indonesian legal system, child protection is regulated in various laws, such as Law No. 35 of 2014, Law no. 17 of 2016, and Law on the Crime of Sexual Violence No. 12 of 2022. This study employs a normative legal research method with a case and legislative approach. The results indicate that legal protection for child victims includes preventive, repressive, and rehabilitative aspects. Although regulations are adequate, implementation in the field still faces obstacles such as the victims' fear of reporting and the limitations of law enforcement officers. In the analyzed case, the defendant was sentenced to 13 years in prison and a fine of Rp. 60 million, reflecting serious efforts in law enforcement. This study emphasizes the importance of synergy among the state, family, and community to create effective protection for children.